Analisis Pengaruh Kebijakan Pembatasan PPKM terhadap Harga Saham pada Perusahaan Makanan dan Minuman serta Perusahaan Ritel yang Terdaftar di BEI pada Tahun 2020-2021 - Nathasia, Julia; Riswan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze and identify the impact of the Community Activity Restrictions (PPKM) policy on share prices in food and beverage and retail companies listed on the Indonesia Stock Exchange (BEI) during 2020-2021 during the COVID-19 pandemic. This research uses quantitative analysis methods on the population of food and beverage and retail companies listed on the IDX during that period. From the survey sample selection criteria, four food and beverage companies and four retail companies were selected to be included in the survey. The results of the analysis and discussion show several conclusions, namely; (1) There are differences in share values in consumer goods companies in Indonesia before and after the PPKM announcement. Based on analysis, the average share value of the food and beverage sector and retail companies listed on the IDX has decreased after the announcement of PPKM in Indonesia. (2) Descriptive data shows that the difference in share value indicates that information related to PPKM policies can significantly influence share value.